Biochemical and photochemical feedbacks of acute Cd toxicity in Juncus acutus seedlings: The role of non-functional Cd-chlorophylls. (20th December 2015) - Santos, D.; Duarte, B.; Caçador, I.
Abstract: The increasing metal pollution in salt marshes and its influence on the plants that inhabit these ecosystems, has become a major concern with serious implications on the species establishment. Juncus acutus is a highly common halophyte specie in Portuguese marshes. Seeds from his specie were exposed to a range of different Cd concentrations (0.05, 0.1, 0.5 and 1 μM) in order to evaluate the effects of acute Cd stress on seed germination and growth as well as on seedling pigment composition, photosynthetic apparatus and oxidative stress biomarkers. Seedling length was higher than in control in every Cd treatment, however biomass showed a decrease. It was also observed that increasing Cd treatments, lead to a proportional increase in the Cd tissue concentration. Also the Cd-substituted chlorophylls showed an increase with increasing Cd doses that were applied. This substitution results in a non-functional chlorophyll molecule, highly unstable under moderate light intensities which inevitably reduces the efficiency of the LHC II. As consequence, there was a decrease in the use-efficiency of the harvested energy, leading to a decay in the photosynthetic capacity and energy accumulation, which was dissipated as heat. As for the antioxidant enzymes, SOD and APX presented higher activity, responding to increasing cadmium concentrations. Thus, becomes evident that Cd affects negatively, both biochemically and photochemically, the establishment by seed process of J. acutus highlighting the potential of the use of this specie seed as potential sentinel and ecotoxicity test in extreme conditions.